Dark-Induced Senescence Causes Localized Changes in DNA Methylation. Issue 2 (2nd December 2019) - Trejo-Arellano, Minerva S.; Mehdi, Saher; de Jonge, Jennifer; Dvorák Tomastíková, Eva; Köhler, Claudia; Hennig, Lars
Abstract : Senescence in Arabidopsis causes a massive transcriptional down-regulation of the machinery safeguarding the integrity and maintenance of the chromatin, the senescent methylome however, remains stable. Abstract: Senescence occurs in a programmed manner to dismantle the vegetative tissues and redirect nutrients towards metabolic pathways supporting reproductive success. External factors can trigger the senescence program as an adaptive strategy, indicating that this terminal program is controlled at different levels. It has been proposed that epigenetic factors accompany the reprogramming of the senescent genome; however, the mechanism and extent of this reprogramming remain unknown. Using bisulphite conversion followed by sequencing, we assessed changes in the methylome of senescent Arabidopsis ( Arabidopsis thaliana ) leaves induced by darkness and monitored their effect on gene and transposable element (TE) expression with transcriptome sequencing. Upon dark-induced senescence, genes controlling chromatin silencing were collectively down-regulated. As a consequence, the silencing of TEs was impaired, causing in particular young TEs to become preferentially reactivated. In parallel, heterochromatin at chromocenters was decondensed. Despite the disruption of the chromatin maintenance network, the global DNA methylation landscape remained highly stable, with localized changes mainly restricted to CHH methylation. Together, our data show that the terminal stage of plant life is accompanied by global changes in chromatin structure but only localized changes in DNA methylation, adding another example of the dynamics of DNA methylation during plant development.